Analysis of knowledge in the interpretation of radiographic images of students of a Dentistry course (Research, Society and Development, 2020)
Radiography is the complementary exam most used by dental surgeons in dental practice and when associated with clinical data, it allows a better identification of some changes and consequently a correct treatment. The objective of this research was to evaluate the level of knowledge of students from the last period, enrolled in the discipline of Integrated Clinic of the Dentistry Course of the Faculdade Patos de Minas - FPM in the second semester of 2020, regarding the precision of diagnosis and treatment decision when analyzing periapical radiographs of several situations found in the clinical routine. The survey consisted of an online questionnaire application with 11 sections. In the first 10 sessions, an periapical radiography of frequent dental routine situations was exposed. For each image there was a question regarding the diagnosis and another question about treatment option. In the 11th section, the students answered which image was the most difficult to interpret. A low percentage of correct answers was observed – only 62.16% (37/23) of the sample answered correctly half or less of the amount of radiographs presented for analysis. When diagnosis and conduct were assessed separately, 69% (37/25) of respondents correctly interpreted the radiographic image and 46% (37/17) were wrong in the clinical conduct. Image 10 showed the highest percentage of difficulty 38% (37/14), according to the responses. This study observed weaknesses related to the interpretation of images less common in the dental clinic and research with more comprehensive methodologies can offer more accurate results regarding the interpretative capacity and treatment decision in relation to radiographic images.